Role of Segregated Iron at Grain Boundaries on Mg Corrosion. Issue 2 (13th January 2018) - Mercier, Dimitri; Światowska, Jolanta; Zanna, Sandrine; Seyeux, Antoine; Marcus, Philippe
Abstract : To elucidate the role of noble metal impurities on corrosion of Mg, 3D time-of-flight secondary ion mass spectrometry (ToF-SIMS) imaging in combination with X-ray photoelectron spectroscopy and optical microscopy measurements were carried out on Mg samples (99.9%) before and after Mg polarization at EOCP +0.5 V in 0.1 M NaCl. A significant segregation of Fe (and of Mn and Al) metallic impurities at grain boundaries (GBs) was observed on the Mg surface by 3D ToF-SIMS. A 3-step mechanism of Mg corrosion was proposed, including a catalytic effect of Fe segregated at the GBs on the hydrogen evolution reaction (HER). In the 1 st stage, the initiation of Mg corrosion is accompanied by the HER occurring over Fe impurities segregated at GBs leading to formation of small circular defects, and propagation with occurrence of dark filiform-like pattern corrosion enriched in Cl − . In the 2 nd stage, segregated Fe metallic particles are released by Mg matrix undermining, and are dissolved into Fe 2+ ions and in the 3 rd stage a redeposition of Fe in the clear areas of Mg surfaces, corresponding to areas with low concentration of Cl −, takes place.